PENGARUH FASILITAS DAN KUALITAS PELAYANAN TERHADAP KEPUASAN PELANGGAN HOTEL BUKIT SERELO LAHAT - Nidyawati, Nidyawati; Hartini, Indra (Universitas Muhammadiyah Palembang, 2021)
Purpose The purpose of this study was to determine and analyze the effect of facilities on customer satisfaction at Hotel Bukit Serelo Lahat, to determine and analyze the effect of service quality on customer satisfaction at Hotel Bukit Serelo Lahat and to determine and analyze the effect of facilities and service quality together on hotel customer satisfaction. Serelo Lahat Hill.Design / methodology Primary data in this study were obtained by distributing questionnaires to 55 customers of Hotel Bukit Serelo Lahat. The data analysis technique used was the SPSS version 23.0 application, using data testing and statistical testing.Findings The results of data analysis on the variables studied, namely facilities and service quality indicate an influence on customer satisfaction at Hotel Bukit Serelo Lahat simultaneously and partially.